Determinants of employee skills' level and utilization in SMEs in the Republic of North Macedonia - Piperkova, Irina; Lozanoska, Aleksandra; Davitkovska, Elena (International Academic Institute, 2020)
Recent research shows that continuous skills upgrading is paramount to achieving competitiveness and sustainability of both individuals at the labour market and the firms. Due to the dynamic business changes, firms permanently expect higher creativity, innovation and initiative from their employees, hence making sure that they possess cutting-edge knowledge, skills and abilities. Nevertheless, firms cannot capitalize solely on the existence of employees’ skills i.e. full utilization of employees’ skills is necessary for achieving competitiveness. Thus, the determinants that influence the level and utilization of employee skills are crucial for firms as well. In this paper, the recruitment process and training are recognized as factors that affect skills level, whereas the methods of motivation determine skills utilization. The results of the empirical analysis on a sample of SMEs in the Republic of North Macedonia indicate that major challenges which firms face during the process of recruitment pertain to lack of applicants’ skills and small number of applicants. Also, almost 60% of the firms either announce only primary vacancy requirements or, although thoroughly defined, do not include the requirements in the vacancy announcement. As for the skills upgrading, about 50% of the firms organized one to three trainings in the last three years, mainly pertaining to improvement of job-specific skills of primary employees. Almost one fifth of firms did not organize any training. The motivation methods are highly important not only to boost employees’ willingness to upgrade their skills but also to fully utilize them in their working activities. The findings indicate that more than half of the firms motivate their employees by providing bonuses and rewards, and by taking employees’ opinion into account. Additional motivating factor refers to employee participation, in particular, including employees in the process of new product/service development.
Keywords: employee skills level, skills utilization, skill determinants, recruitment, training, motivation